Sustainable Development Goals (SDGs) Village Governance on Zero Poverty: A Case of Suci Village, Garut Regency - Nabila Kamila, Nabila Kamila; Rd Ahmad Buchari (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2024)
This study examines the role of Sustainable Development Goals (SDGs) Village Governance on Zero Poverty: A Case of Suci Village, Garut Regency. Several issues were identified in the governance processes aimed at supporting the SDGs goal of a poverty-free village in Suci. These issues include suboptimal transparency in identifying the poor population, low public participation in the Village Development Planning Assembly (musrenbangdes), and inefficiencies in utilizing available human resources. The objective of this study is to describe the implementation of good village governance in supporting the SDGs goal of a poverty-free village in Suci. The theoretical framework is based on Henk Addink's (2019) principles of good governance, which include propriety, transparency, participation, effectiveness, accountability, and human rights. This qualitative study employs data collection techniques such as interviews, observations, and documentation. The findings indicate that while the governance in Suci Village has generally been effective in supporting the SDGs goal of zero poverty, challenges remain. These challenges include data inconsistencies between village and local government, low community engagement in musrenbangdes, and suboptimal government performance due to limited human resources.